Sistem Informasi Geografis Fasilitas Kesehatan di Tuntungan Berbasis Android - Fajrillah; Lusiah (Bulletin of Computer Science Research, 2023)
The use of Android phone data frames is growing rapidly in today's world. He is known for his ability to retrieve data quickly and accurately, especially during crises. His one of human information needs is information about medical facilities. The purpose of this article is to provide an Android-based application that helps an individual obtain data from his Tuntungan Public Health Authority in various ways. The method used to improve the framework in this review is his waterfall model consisting of five phases: requirements identification, system design, code preparation, program testing, and program implementation. In addition, program development using Visual Studio Code, Flutter SDK, Mobile Emulator, Mobile Emulator and Firebase integration as information base. During this inspection, the use of the Geographic Information System "GIS" was found to be inadequate. Because the people of Tuntungan ran well according to their ability. This Android-based application system can display a map showing the location of medical facilities on the Internet and detailed information about medical facilities in Tuntugan Province.